Polyimide / polyacid-based composite photocatalyst as well as preparation method and application thereof

By preparing polyimide/polyacid composite photocatalysts, the POM-π interaction between polyimide and polyacid was solved, and the problems of narrow photoresponse range, difficulty in recycling and poor degradation were achieved. High efficiency, wide visible light response, easy recovery and stable photocatalytic effects.

CN119488953APending Publication Date: 2025-02-21JIANGSU OCEAN UNIV +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411641781.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing polyacid photocatalysts have problems with narrow photoresponse range, difficulty in recovery, and poor continuous degradation of substrates and intermediates.

Method used

By reacting and thermally polymerizing amine compounds, polyacid compounds and acid anhydride compounds, a polyimide/polyacid composite photocatalyst is prepared, and the POM-π interaction between polyimide and polyacid is improved. Photogenerated carrier separation and transmission efficiency, visible light absorption range, solubility and recyclability of photocatalysts.

Benefits of technology

The visible light response effect of the polyimide/polyacid-based composite photocatalyst is achieved, with a wide visible light absorption range, easy to recover and high stability, and the problem of narrow light response range, difficulty in recycling and poor degradability of the polyacid photocatalyst is solved. , and exhibits continuous and efficient decomposition effects in the field of photohydrogen production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119488953A_ABST
    Figure CN119488953A_ABST
Patent Text Reader

Abstract

The invention discloses a polyimide / polyacid-based composite photocatalyst as well as a preparation method and application thereof, and belongs to the technical field of photocatalytic materials. The preparation method of the polyimide / polyacid-based composite photocatalyst comprises the following steps: (1) mixing and reacting an amine compound, a polyacid compound and a solvent to obtain a solid product; and (2) mixing the solid product with an anhydride compound, and carrying out thermal polymerization to obtain the polyimide / polyacid-based composite photocatalyst. The POM-pi interaction of polyimide and polyacid in the photocatalyst can improve the visible light absorption range and solubility of polyacid, improve the photon-generated carrier separation and transmission efficiency and recoverability of the photocatalyst, and in addition, the photocatalyst has the advantages of long service life, high stability and low cost. The method can play a continuous and efficient decomposition role in the field of hydrogen production by decomposing water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photocatalytic materials, and more specifically relates to a polyimide / polyacid-based composite photocatalyst and a preparation method and application thereof. Background Art

[0002] Polyoxometalates are a class of nanoscale metal-oxygen cluster compounds containing transition metal ions (such as W, V, Mo, etc.), referred to as polyoxometalates (POMs). Polyoxometalates can be used as electron acceptors and photogenerated charge transfer media due to their high thermal stability, high negative charge and redox potential, catalytic ability, and many unique properties of ligands. At present, polyoxometalates have shown great application potential in the fields of photocatalysis, photoelectrochemistry, and solar energy utilization. While achieving many excellent results, polyoxometalates also face some challenges. On the one hand, due to the high negative charge of polyoxometalates, polyoxometalates have good solubility and are easily soluble in water or other polar organic solvents, becoming homogeneous catalysts and difficult to recycle; on the other hand, polyoxometalates have a narrow light response range, and expanding their spectral absorption is of utmost importance; in addition, polyoxometalates have poor stability and usually require the introduction of additional promoters to continuously degrade substrates and intermediates. Therefore, how to improve the light absorption and solubility of polyoxometalates and prepare visible light-driven, efficient, and recyclable polyoxometalates-based photocatalysts is an important research direction in the field of polyoxometalates photocatalysts. Summary of the invention

[0003] The purpose of the present invention is to provide a polyimide / polyacid-based composite photocatalyst and a preparation method and application thereof, which has good visible light response effect, wide visible light absorption range, easy recovery and high stability, and solves the problems of currently commonly used polyacid photocatalysts such as narrow light response range, difficult recovery, and poor continuous degradation of substrates and intermediates.

[0004] To achieve the above object, the present invention provides the following solutions:

[0005] One of the technical solutions of the present invention is to provide a method for preparing a polyimide / polyacid-based composite photocatalyst, comprising the following steps:

[0006] (1) mixing an amine compound, a polyacid compound and a solvent to react to obtain a solid product;

[0007] (2) The solid product and the acid anhydride compound are mixed and then thermally polymerized to obtain the polyimide / polyacid-based composite photocatalyst.

[0008] The present invention utilizes amine compounds, polyacid compounds and acid anhydride compounds to realize the synthesis of polyimide / polyacid-based composite photocatalysts through simple reactions and thermal polymerization, wherein the conjugation of polyimide is extended to the keggin structure of the polyacid and the delocalization of electrons occurs in the POM-based organic-inorganic hybrid material skeleton, resulting in the POM-π interaction between the polyimide and the polyacid, thereby improving the photogenerated carrier separation and transmission efficiency, visible light absorption range, solubility and recyclability of the photocatalyst, and solving the problems of narrow light response range and difficult recycling of the currently commonly used polyacid photocatalysts.

[0009] The polyimide / polyacid-based composite photocatalyst obtained by the invention is recovered through the operation steps of centrifugation, washing and drying in sequence, and the recovery method is simple.

[0010] Preferably, the amine compound includes one or more of p-phenylenediamine, melamine and tri(4-aminophenyl)amine; the polyacid compound includes H3PMo 12 O 40 、H3PW 12 O 40 and H6O 39 S W 12 The solvent includes water and / or methanol; the anhydride compound includes one or more of naphthalene-1,4,5,8-tetracarboxylic dianhydride, perylene-3,4,9,10-tetracarboxylic dianhydride and pyromellitic anhydride.

[0011] Preferably, the mass ratio of the amine compound, the polyacid compound and the acid anhydride compound is 0.5-2:3-5:2-4.

[0012] Preferably, the mixing step in step (1) comprises: dissolving the amine compound and the polyacid compound in solvents respectively to form an amine compound solution and a polyacid compound solution; and dropping the polyacid compound solution into the amine compound solution.

[0013] Preferably, the concentration of the amine compound in the amine compound solution is 0.08-0.085 mol / L; the concentration of the polyacid compound in the polyacid compound solution is 0.08-0.09 mol / L; the dissolution temperature is independently 85-95°C; the dripping speed is 4-5 drops / s, and the dripping temperature is 85-95°C.

[0014] More preferably, the dissolution time is determined according to actual conditions to ensure complete dissolution.

[0015] Preferably, the reaction temperature is 85-95°C, and the reaction time is 2-4h; after the reaction is completed, washing and drying steps are also included, and the washing comprises: washing the precipitate obtained in the reaction of step (1); the reagent used for the washing is water at 70-80°C; the drying temperature is 70-80°C, and the drying time is 10-12h.

[0016] More preferably, the mixing and reaction in step (1) are carried out under stirring in an oil bath.

[0017] Preferably, the mixing in step (2) is grinding mixing; the mixing time is 10 to 15 minutes.

[0018] Preferably, the temperature of the thermal polymerization is 300-350° C., the heating rate of the thermal polymerization is 5-7° C. / min, and the time of the thermal polymerization is 3-5 h.

[0019] The second technical solution of the present invention: providing a polyimide / polyacid-based composite photocatalyst prepared by the preparation method of the polyimide / polyacid-based composite photocatalyst.

[0020] The third technical solution of the present invention is to provide the application of the polyimide / polyacid-based composite photocatalyst in photocatalytic water decomposition to produce hydrogen.

[0021] The polyimide / polyacid-based composite photocatalyst prepared by the present invention has a matching energy band structure, making it suitable for photocatalytic water decomposition to produce hydrogen. The polyimide / polyacid-based composite photocatalyst prepared by the present invention can play a continuous and efficient decomposition role in the field of photocatalytic water decomposition to produce hydrogen.

[0022] The present invention discloses the following technical effects:

[0023] (1) Polyimide (PI) is an organic polymer containing cyclic imide groups in the molecular chain. It is prepared by a simple green thermal condensation reaction of electron donor aromatic amine and electron acceptor anhydride chain. By changing the structure of the comonomer and the condensation temperature, the band gap of polyimide can be adjusted within a large visible light response range (1.9-3eV). In addition, designing the structure of polyimide at the molecular level can also change the heat resistance, solubility, crystallinity, conductivity, light permeability and mechanical properties of polyimide, so that polyimide can adapt to various application environments. However, there is little research on the preparation of photocatalysts by combining polyacids and polyimides. In view of this, the present invention proposes to synthesize a polyimide / polyacid-based composite photocatalyst by a simple oil bath and thermal polymerization method to solve the problems of the currently commonly used polyacid photocatalysts, such as narrow light response range, difficult recovery, and poor continuous degradation of substrates and intermediates. At the same time, it solves the problem of low efficiency of commonly used polyacid photocatalysts in photolysis of water to produce hydrogen. The synthesis method is simple and low-cost, and can be used for the synthesis of polyimide / polyacid-based composite photocatalysts with various structures based on the diversity of the selected monomer structure types.

[0024] (2) The POM-π interaction between polyimide and polyacid in the polyimide / polyacid-based composite photocatalyst obtained by the present invention can improve the visible light absorption range and solubility of the polyacid, enhance the photogenerated carrier separation, transmission efficiency and recyclability of the photocatalyst, and solve the problems of narrow light response range and difficult recycling of the currently commonly used polyacid photocatalysts.

[0025] (3) The polyimide / polyacid-based composite photocatalyst obtained by the present invention has a long service life and high stability, and can play a continuous and efficient decomposition role in the field of water decomposition to produce hydrogen. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The schematic diagram of the preparation process of naphthalenetetracarboxylic acid imide (PI) described in Comparative Example 1;

[0027] Figure 2 XRD spectra of the photocatalysts described in Example 1, Comparative Example 1 and Comparative Example 2;

[0028] Figure 3 The UV-visible diffuse reflectance spectra of the photocatalysts described in Example 1, Comparative Example 1 and Comparative Example 2 are shown;

[0029] Figure 4 The infrared spectra of the photocatalysts described in Example 1, Comparative Example 1 and Comparative Example 2;

[0030] Figure 5 The fluorescence spectra of the photocatalysts described in Example 1 and Comparative Example 1 are shown;

[0031] Figure 6The nitrogen adsorption-desorption isotherm curves of the photocatalysts described in Example 1 and Comparative Example 1;

[0032] Figure 7 It curve diagram of the photocatalyst described in Example 1 and Comparative Example 1 under visible light irradiation;

[0033] Figure 8 The EIS-Nyquist graphs of the photocatalysts described in Example 1 and Comparative Example 1 under visible light irradiation;

[0034] Fig. 9 The activity result diagram of the photocatalysts described in Example 1 and Comparative Example 1 for photocatalytic decomposition of water to produce hydrogen;

[0035] Fig.10 This is a graph showing the stability results of the photocatalytic decomposition of water to produce hydrogen using the photocatalyst described in Example 1. DETAILED DESCRIPTION

[0036] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0037] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0038] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0039] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0040] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0041] Example 1

[0042] (1) 0.8976 g p-phenylenediamine (Pa) and 3.1 g H3PMo 12 O 40 (PMo) was dissolved in 100 mL and 20 mL of 90°C hot water, respectively, and after dissolving for 30 min, a Pa aqueous solution and a PMo aqueous solution were obtained. Then, the Pa aqueous solution was placed in an oil bath at 90°C and stirred, and the PMo aqueous solution was added dropwise to the Pa aqueous solution at a dropping speed of 5 drops / s. After the addition was completed, the temperature was maintained at 90°C. After treating for 3 h, the solid product was immediately filtered and washed with 70°C hot water for 3 times, and the solid product was dried in an air circulation oven at 80°C for 12 h to obtain an insoluble product, recorded as 5NPMo.

[0043] (2) Grind the 5NPMo obtained in step (1) and 2.23 g of naphthalene-1,4,5,8-tetracarboxylic dianhydride (NTCDA) powder for 10 min, transfer to a 50 mL covered porcelain crucible, heat to 325 ° C in a muffle furnace, set the heating rate to 7 ° C / min, and keep warm for 4 h to obtain the final product naphthalenetetracarboxylic acid imide / H3PMo 12 O 40 The composite photocatalyst is denoted as 5NPI-PMo.

[0044] Example 2

[0045] (1) 0.8976 g p-phenylenediamine (Pa) and 3.1 g H3PMo 12 O 40 (PMo) was dissolved in 100 mL and 20 mL of 90°C hot water, respectively, and after dissolving for 30 min, a Pa aqueous solution and a PMo aqueous solution were obtained. Then, the Pa aqueous solution was placed in an oil bath at 90°C and stirred, and the PMo aqueous solution was added dropwise to the Pa aqueous solution at a dropping speed of 5 drops / s. After the addition was completed, the temperature was maintained at 90°C. After treating for 3 h, the solid product was immediately filtered and washed with 70°C hot water for 3 times, and the solid product was dried in an air circulation oven at 80°C for 12 h to obtain an insoluble product, recorded as 5NPMo.

[0046] (2) Grind the 5NPMo obtained in step (1) and 3.26g of perylene-3,4,9,10-tetracarboxylic dianhydride (PTCDA) powder for 10min, transfer to a 50mL covered porcelain crucible, heat to 325°C in a muffle furnace, set the heating rate to 7°C / min, and keep warm for 4h to obtain the final product perylene tetracarboxylic acid imide / H3PMo 12O 40 Composite photocatalyst.

[0047] Example 3

[0048] (1) 0.8976 g p-phenylenediamine (Pa) and 4.9 g H3PW 12 O 40 (PW) was dissolved in 100 mL and 20 mL of 90°C hot water, respectively, and after dissolving for 30 min, a Pa aqueous solution and a PW aqueous solution were obtained. Then, the Pa aqueous solution was placed in an oil bath at 90°C and stirred, and the PW aqueous solution was added dropwise to the Pa aqueous solution at a dropping speed of 5 drops / s. After the addition was completed, the temperature was maintained at 90°C. After treating for 3 h, the solid product was immediately filtered and washed three times with 70°C hot water, and the solid product was dried in an air circulation oven at 80°C for 12 h to obtain an insoluble product, which was recorded as 5NPW.

[0049] (2) The 5NPW obtained in step (1) and 2.23 g of naphthalene-1,4,5,8-tetracarboxylic dianhydride (NTCDA) powder were ground for 10 min, transferred to a 50 mL covered porcelain crucible, heated to 325 ° C in a muffle furnace, set the heating rate to 7 ° C / min, and kept warm for 4 h to obtain the final product naphthalenetetracarboxylic acid imide / H3PW 12 O 40 Composite photocatalyst.

[0050] Example 4

[0051] (1) 1.0470 g melamine (MA) and 3.1 g H3PMo 12 O 40 (PMo) was dissolved in 100 mL of methanol aqueous solution (methanol: water = 1:2 (v / v)) and 20 mL of 90°C hot water, respectively. After dissolving for 30 min, an aqueous solution of MA methanol and an aqueous solution of PMo were obtained. Then, the aqueous solution of MA methanol was placed in an oil bath at 80°C and stirred, and the aqueous solution of PMo was added dropwise to the aqueous solution of MA at a dropping speed of 5 drops / s. After the dropping was completed, the temperature was maintained at 80°C. After treating for 3 h, the solid product was immediately filtered and washed with 70°C hot water for 3 times. The solid product was dried in an air circulation oven at 80°C for 12 h to obtain an insoluble product, which was recorded as 5NPMo.

[0052] (2) Grind the 5NPMo obtained in step (1) and 2.23 g of naphthalene-1,4,5,8-tetracarboxylic dianhydride (NTCDA) powder for 10 min, transfer to a 50 mL covered porcelain crucible, heat to 325 ° C in a muffle furnace, set the heating rate to 7 ° C / min, and keep warm for 4 h to obtain the final product polyimide / H3PMo 12 O 40 Composite photocatalyst.

[0053] Comparative Example 1

[0054] 0.8976 g of p-phenylenediamine (Pa) and 2.23 g of naphthalene-1,4,5,8-tetracarboxylic dianhydride (NTCDA) were mixed and ground for 10 min, transferred to a 50 mL porcelain crucible with a lid, heated to 325 ° C in a muffle furnace, set the heating rate to 7 ° C / min, and kept warm for 4 h to obtain naphthalenetetracarboxylic acid imide, recorded as PI.

[0055] Comparative Example 2

[0056] H3PMo 12 O 40 (PMo) as a photocatalyst.

[0057] Test example

[0058] Example 1 obtained naphthalene tetracarboxylic acid imide / H3PMo 12 O 40 Composite photocatalyst (5NPI-PMo), photocatalyst naphthalenetetracarboxylic acid imide (PI) obtained in comparative example 1 and photocatalyst H3PMo obtained in comparative example 2 12 O 40 (PMo) for performance testing, the test results are as follows Figures 2 to 10 shown.

[0059] The test standards and methods for each performance are as follows:

[0060] X-ray diffraction (XRD) spectra were acquired on a Bruker AXSD8 Focus using filtered Cu Ka radiation. UV-Vis diffuse reflectance spectra were obtained on a UV-2600 UV-vis spectrophotometer (Shimadzu). Fourier transform infrared (FT-IR) spectra were obtained using a Nicolet iS10 Fourier transform infrared spectrometer. Fluorescence spectra with an excitation wavelength of 380 nm were measured on a VARIANCary Eclipse spectrophotometer. Nitrogen adsorption-desorption isotherms were obtained at 77 K using a Quanta-chrome Auto sorb iQ device.

[0061] Electrochemical performance test: Before the experiment, the sample was degassed under vacuum at 120°C for 12 h. The electrochemical test was carried out on a CHI6660E electrochemical workstation using a standard three-electrode system. Ag / AgCl electrode, Pt sheet and FTO conductive glass on which the sample was deposited were used as reference electrode, counter electrode and working electrode, respectively. The electrolyte solution was a 0.2M NaSO4 aqueous solution. Preparation of the working electrode: 30 mg of the catalyst was dispersed in a centrifuge tube containing 2 mL of ethanol and 50 μL of perfluorosulfonic acid-polytetrafluoroethylene copolymer (Nafion) solution, and then ultrasonically dispersed evenly. The suspension was transferred to a 14 cm 2 The exposed area of ​​the catalyst is 3 cm 2 Finally, the working electrode was obtained by drying at room temperature.

[0062] The photocurrent test (it curve) uses a 300W xenon lamp (CELHXF300, AULIGHT) as the light source. To reduce the influence of experimental errors, the light source is irradiated from the back of the FTO glass substrate.

[0063] Electrochemical impedance spectroscopy (EIS) was measured using a CHI700E electrochemical workstation in a 0.2M NaSO4 aqueous solution at a voltage of -0.2 V and a frequency range of 0.01 Hz to 10 kHz. The electrodes used in the EIS test were the same as those used in the photocurrent test.

[0064] Figure 2 The XRD spectra of the photocatalysts described in Example 1, Comparative Example 1 and Comparative Example 2 are shown. Figure 3 The UV-visible diffuse reflectance spectra of the photocatalysts described in Example 1, Comparative Example 1 and Comparative Example 2 are shown. Figure 4 The infrared spectra of the photocatalysts described in Example 1, Comparative Example 1 and Comparative Example 2 are shown in FIG. Figures 2 to 4 It can be seen that naphthalenetetracarboxylic acid imide and naphthalenetetracarboxylic acid imide / H3PMo 12 O 40 The composite photocatalyst was successfully prepared, and the visible spectrum absorption range of the composite photocatalyst was significantly expanded.

[0065] Figure 5 The fluorescence spectra of the photocatalysts described in Example 1 and Comparative Example 1 are shown in FIG. Figure 5 It can be seen that naphthalenetetracarboxylic acid imide / H3PMo 12 O 40 The composite photocatalyst has stronger conjugation, which leads to a shift of the light absorption range to longer wavelengths.

[0066] Figure 6 The nitrogen adsorption-desorption isotherm curves of the photocatalysts described in Example 1 and Comparative Example 1 are shown in FIG. Figure 6It can be seen that the nitrogen adsorption-desorption isotherms of the photocatalysts are both type IV isotherms with H3 hysteresis loops, indicating that the two catalysts are mesoporous materials formed by layered stacking.

[0067] Figure 7 It curve diagram of the photocatalyst described in Example 1 and Comparative Example 1 under visible light irradiation. Figure 8 The EIS-Nyquist graphs of the photocatalysts described in Example 1 and Comparative Example 1 under visible light irradiation are shown in FIG. Figure 7 and 8 It can be seen that under visible light irradiation, naphthalene tetracarboxylic acid imide / H3PMo 12 O 40 The photocurrent density of the composite photocatalyst is larger, indicating that the carrier separation performance of the photocatalyst has been greatly improved. In addition, the electrochemical impedance spectroscopy (EIS) further revealed the charge transfer characteristics of the sample. The experimental results showed that naphthalene tetracarboxylic acid imide / H3PMo 12 O 40 The charge transfer resistance of the composite photocatalyst is lower.

[0068] Fig. 9 The results of the photocatalytic decomposition of water to produce hydrogen by the photocatalysts described in Example 1 and Comparative Example 1 are shown in FIG. Fig. 9 It can be seen that the naphthalene tetracarboxylic acid imide / H3PMo obtained by the present invention 12 O 40 The composite photocatalyst has higher photocatalytic water decomposition and hydrogen production activity than naphthalenetetracarboxylic acid imide.

[0069] Fig.10 This is a graph showing the stability of the photocatalyst described in Example 1 for photocatalytic decomposition of water to produce hydrogen. Fig.10 It can be seen that after 20 hours of continuous photocatalytic decomposition of water to produce hydrogen, the naphthalene tetracarboxylic acid imide / H3PMo obtained in the present invention 12 O 40 The composite photocatalyst can still retain the same photocatalytic water splitting hydrogen production ability as at the initial stage.

[0070] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0071] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a polyimide / polyacid-based composite photocatalyst, characterized in that: The steps include: (1) mixing an amine compound, a polyacid compound and a solvent to react to obtain a solid product; (2) The solid product and the acid anhydride compound are mixed and then thermally polymerized to obtain the polyimide / polyacid-based composite photocatalyst.

2. The preparation method according to claim 1, characterized in that: The amine compound includes one or more of p-phenylenediamine, melamine and tri(4-aminophenyl)amine; the polyacid compound includes H3PMo 12 O 40 、H3PW 12 O 40 and H6O 39 S W 12 The solvent includes water and / or methanol; the anhydride compound includes one or more of naphthalene-1,4,5,8-tetracarboxylic dianhydride, perylene-3,4,9,10-tetracarboxylic dianhydride and pyromellitic anhydride.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the amine compound, the polyacid compound and the acid anhydride compound is 0.5-2:3-5:2-4.

4. The preparation method according to claim 1, characterized in that: The mixing step in step (1) comprises: dissolving the amine compound and the polyacid compound in solvents respectively to form an amine compound solution and a polyacid compound solution; and dropping the polyacid compound solution into the amine compound solution.

5. The preparation method according to claim 4, characterized in that: The concentration of the amine compound in the amine compound solution is 0.08-0.085 mol / L; the concentration of the polyacid compound in the polyacid compound solution is 0.08-0.09 mol / L; the dissolution temperature is independently 85-95°C; the dripping speed is 4-5 drops / s, and the dripping temperature is 85-95°C.

6. The preparation method according to claim 1, characterized in that: The reaction temperature is 85-95°C, and the reaction time is 2-4h. After the reaction is completed, washing and drying steps are also included. The washing includes: washing the precipitate obtained in the step (1); the reagent used for the washing is 70-80°C water; the drying temperature is 70-80°C, and the drying time is 10-12h.

7. The preparation method according to claim 1, characterized in that: The mixing in step (2) is grinding mixing; the mixing time is 10 to 15 minutes.

8. The preparation method according to claim 1, characterized in that: The temperature of the thermal polymerization is 300-350° C., the heating rate of the thermal polymerization is 5-7° C. / min, and the time of the thermal polymerization is 3-5 hours.

9. The polyimide / polyacid-based composite photocatalyst prepared by the method for preparing the polyimide / polyacid-based composite photocatalyst according to any one of claims 1 to 8.

10. Use of the polyimide / polyacid-based composite photocatalyst according to claim 9 in photocatalytic water decomposition to produce hydrogen.

Citation Information

Patent Citations

  • Photocatalytic material polyimide, as well as preparation method and applications thereof

    CN104277219A

  • Large Pi system polyimide cross-linked polymer for negative electrode of lithium ion battery

    CN104953123A

  • Broad-spectrum-response polynaphthalimide photocatalytic material and preparation method thereof

    CN109880089A

  • Polyimide with high specific surface area and high crystallinity and preparation method and application thereof

    CN113336941A

  • Polyimide / silver phosphotungstate photocatalyst as well as preparation method and application thereof

    CN117299210A